PENGARUH KEGIATAN EKSTRAKURIKULER SENI RUPA TERHADAP PRESTASI BELAJAR SISWA DALAM MATA PELAJARAN SENI BUDAYA DI SEKOLAH MENENGAH PERTAMA NEGERI 25 PADANG - Rahmatul Umika, Drs. Abd. Hafiz, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of this research is to know the learning achievement of students who take extracurricular activities with those who do not take part in extracurricular activities in sub-arts art subjects. The results of this study show that the average value of students who take extracurricular activities with those who don not is 89.05, and 78,68 value of t-count > t-table, the positif influence of extracurricular activities on student learning achievement.Keywords : extracurricular activities. learning achievement